Structural dynamics for engineers - Buchholdt, H. A. 1925- (Thomas Telford, 1997)
This book has been written to provide practising engineers with an easily understandable introduction to the dynamics of civil engineering whilst ensuring that they acquire an understanding of the theories that form the basis of computer packages.